The Impact of Technology Change, Deindustrialization, and Internationalization of Trade on Earnings Inequality An International Perspective - Mary Joyce; Peter Gottschalk (Luxembourg Income Study (LIS), 1992)
Looks into the links between structural change in industrialized countries and the rise of income inequality. Includes a useful literature review on inequality in the U.S.
Keywords: 330